The lagal text and schedules : (Cambridge University Press, 2002)
This CD-ROM database contains the fully updated WTO services and schedules of services commitments and/or MFN exemptions for WTO member countries in English, plus the Legal Texts in English, French and Spanish. This material has never been available in one source before; much has been unavailable in any form.